1999
DOI: 10.1159/000012325
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of Professional Fulfilment and Exhaustion in Mental Health Personnel: The Importance of Organisational and Individual Factors

Abstract: Background: Mental health personnel are at high risk for mental illness, burnout and suicide. Previous studies of this group of professionals have indicated the importance of organisational factors in explaining burnout, or exhaustion, and work satisfaction. This study looks more systematically at the contribution of organisational and individual factors to work-related exhaustion and to professional fulfilment, an expanded version of job satisfaction. Methods: A cross-sectional study of 1, 051 psychiatrists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 22 publications
0
71
0
5
Order By: Relevance
“…These issues, he argued, could equally apply to mental health nurses. Thomsen et al (1999), however, found that gender, level of self-esteem, the number and nature of the demands of home life, and the ability to devise and implement coping mechanisms were the significant indicators of nurses' mental health. Prosser et al (1996) compared stress and coping strategies among hospital and community-based mental health nurses.…”
Section: Mental Health Nursesmentioning
confidence: 94%
See 1 more Smart Citation
“…These issues, he argued, could equally apply to mental health nurses. Thomsen et al (1999), however, found that gender, level of self-esteem, the number and nature of the demands of home life, and the ability to devise and implement coping mechanisms were the significant indicators of nurses' mental health. Prosser et al (1996) compared stress and coping strategies among hospital and community-based mental health nurses.…”
Section: Mental Health Nursesmentioning
confidence: 94%
“…Along with the closure of psychiatric institutions, the role of mental health nurses underwent radical change, encompassing such areas as supporting and educating clients and their carers, as well as non-mental health care colleagues with whom they came into contact. Stress and coping in mental health nursing have been widely discussed because of the growing evidence that mental health workers are at high risk of mental illness, burnout and suicide Thomsen et al, 1999). The reasons for this are complex and poorly understood.…”
Section: Mental Health Nursesmentioning
confidence: 99%
“…Burnout has been studied in different areas of Medicine such as Oncology, Intensive and Palliative Care Units, and Psychiatric Services, suggesting a higher prevalence among general and hospital practitioners who face chronic or life-threatening diseases (Olkinuora et al, 1990;Catalan et al, 1996;Ramirez et al, 1998;Thomsen et al, 1999;Grassi and Magnani, 2000;Graham and Ramirez, 2002;Fothergill et al, 2004;Embriaco et al, 2007).…”
mentioning
confidence: 99%
“…Social service occupations, e.g. medical and healthcare personnel, teachers, policemen and social insurance personnel often have specific mentally stressful work situations (Andersson-Felé, 2002;Dysting, 1996;Eklund & Rahm Hallberg, 2000;Fochsen et al, 2005;Isberg, 2002;Jönsson, 2005;Jönsson et al, 2003;Lawoko et al, 2004;Lill, 2007;Lipsky, 1980;Michélsen et al, 1999;Nilsson, 2004;Johansson & Olofsson, 1996;Salinsky & Sackin, 2004;Sundgren Grinup et al, 1996;Thomsen et al, 1999). They are the link between the clients/patient and the regulations/organisation and need to deal with and take care of other people's personal problems and sorrow at the same time as they need to take care of their own reactions (Lipsky, 1980).…”
Section: Mental Work Environmentmentioning
confidence: 99%